Ovine enzootic abortion disease seroprevalence in small ruminants around the world: a systematic review. - Kifouly, A. H.; OKUNLOLA, Michael; BOKO, KADOÉITO CYRILLE; Allowanou, Georcellin; Challaton, Kétomon Pierre (My University, 2023)
Chlamydia abortus is a causative agent of Ovine Chlamydiosis or Ovine Enzootic Abortion (OEA) or Enzootic Abortion of Ewes (EAE) and can be transmitted to humans, especially pregnant women during the lambing or kidding season from sheep, and goats, from infected flocks. The objective of this study was to estimate the pooled prevalence of chlamydial abortus infections in small ruminants. The study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Relevant studies were retrieved from PubMed, Scopus, Web of Science, and Google Scholar from 2001 to 2022. The retrieved studies were screened for eligibility and important data were extracted from the included studies. The quality of each included study was evaluated. Of 153 studies, 33 (with a total of 45453 samples) met the inclusion criteria and were included in the meta-analysis. The pooled prevalence of chlamydial infections in small ruminants was 13.4%. Among continents, the average prevalence of chlamydial abortus infections was highest in Asia (48.5%) and lowest in North America (3.0%) This systematic review emphasizes the global paucity of data on the prevalence of Chlamydia infection in sheep and goats. Despite this, studies show a rather high frequency of C. abortus infection in small ruminants. This geographical variance emphasizes the necessity of a regional strategy to chlamydia infection prevention and management in small ruminants, taking into account regional differences and risk factors to avoid its spread and limit the hazards associated with it.
Keywords: Chlamydia abortus; small ruminants (Sheep and Goats); seroprevalence; and World